(3GdLhGgQs - (3SYjO feOHhT , WGgQ Hf bGSe Hf CMeO GdCfUGQj, SYjO feOHhT,J (B771 (3g` s
(3ChdgG (B:s
(3CeG HYO adG fYeI ddg JYGdi Ydi YHOg CYXe ef GdEjeGf hGdYHGOI hdG hSjdI EdjgeG Shi JMUjd YdegeG HfhQ GdHUjQI s
(3BNQgG (B:s
(3Efg gh GdZaGQ GdhgGH ddeDefjf SHjd GdUhGH hEdjg GdeQLY hGdeBH s
(3GdfSNI HgG MhGTs
(3HChdg agQSJ ddeNWhWs
(3fSNI KGfjI s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdMfajs